HINSIDES FORESTILLINGEN OM DET FORUDSIGELIGE: Om at være drikkende ikke-alkoholiker blandt ikke-drikkende alkoholikere - Steffen, Vibeke (Tidsskriftet Antropologi, 1995)
Vibeke Steffen: Beyond the Notion of Predictability - on Being a Drinking Non- Alcoholic among Non-Drinking Alcoholics This article argues that anthropological fieldwork is betler understood as a research strategy than as a standard set of methods. Based on the author’s experience as a participantobserver in a treatment program for alcoholism in Denmark, the article describes how the interaction with informants and the character of the study to a great extent determined the actual research process. The meaning of participation became especially central as informants insisted on the researcher’s active participation in therapy. This leads to a discussion of the meaning of participation as a way of sharing experience and the importance of unplanned communication as a way of obtaining information. The kind of relationships that informants are prepared to share with us as researchers, and the kind of relationships that we as researchers are prepared to enter into with our informants, are seen as an ongoing process of negotiation creating the basic conditions for knowledge. Thus, the author concludes that it makes no sense to try to describe anthropological methods as techniques of data collection separate from the concrete research process.